Plasma tumor mutation burden is associated with clinical benefit in patients with non-small cell lung cancer treated with anti-programmed death-1 monotherapy. (December 2022) - Lee, Jii Bum; Park, Hyung Soon; Choi, Su Jin; Heo, Seong Gu; An, Ho Jung; Kim, Hye Ryun; Hong, Min Hee; Lim, Sun Min; Chang, Kyle; Quinn, Katie; Odegaard, Justin; Shim, Byoung Yong; et al.
Background: The clinical utility of plasma tumor mutational burden (pTMB) requires further validation. Herein, the pTMB and genetic alterations were investigated as predictive biomarkers for anti-PD-1 monotherapy outcome in metastatic non-small cell lung cancer (NSCLC). Methods: The GuardantOMNI panel (Guardant Health) was used to identify pTMB and genetic alterations. Data from 99 patients with metastatic NSCLC treated with pembrolizumab or nivolumab in first-, second-, or third-line settings between June 2016 and December 2020 were collected. Associations between pTMB and clinical benefit rate (CBR, stable disease ⩾6 months or partial response), progression-free survival (PFS), and overall survival (OS) were assessed. Results: Median pTMB in 84 patients was 10.8 mutations/megabase (mut/Mb). Histological analyses revealed that 61 and 36% of the patients had adenocarcinomas and squamous NSCLC, respectively. Most patients were treated with nivolumab (74%) and most anti-PD-1 agents were administered as second-line treatment (70%). The median follow-up duration was of 10.9 months (range, 0.2–40.7). Patients with high pTMB (⩾19 mut/Mb) had a higher CBR (69%) compared with low pTMB patients (33%; p  = 0.01). ARID1A ( p  = 0.007) and either ERBB2 or KIT mutations ( p  = 0.012) were positive and negative determinants, respectively, for clinical benefit. Multivariate analysis further showed that high pTMB was an independent predictive biomarker for both PFS [hazard ratio (HR) = 0.44, 95% confidence interval (CI): 0.22–0.88, p  = 0.02] and OS (HR = 0.37, 95% CI: 0.18–0.76, p  = 0.007). Conclusion: High pTMB (⩾19 mut/Mb) is significantly associated with CBR in patients with NSCLC treated with anti-PD-1 agents.